EFEKTIVITAS MODEL DESAIN PROBLEM BASED LEARNING DENGAN PENGGUNAAN JOBSHEET DALAM PEMBELAJARAN KONSTRUKSI BANGUNAN DI LINGKUP SMK - Egi Noruza (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Problem Based Learning (PBL), is a learning model that is able to provide experience and an innovative learning model that can provide active learning conditions for students to solve a problem through the stages of scientific methods so that students can learn knowledge related to the problem as well as have the skills to solve problems. The main objective of PBL is to develop critical thinking, analytical, collaboration, and problem-solving skills in students. Jobsheet is one of the teaching materials that can support learning in the classroom. This study examines the effectiveness of the problem-based learning design model with the use of Jobsheet In the context of Building Construction learning with the use of Problem Based Learning (PBL), the use of jobsheets is very effective in improving learning outcomes and developing the potential abilities of students. This research shows that the Problem Based Learning learning approach that uses jobsheets as a complement is an innovation that refers to the general syntax framework of Problem Based Learning.